2022
DOI: 10.3389/ti.2022.10751
|View full text |Cite
|
Sign up to set email alerts
|

Early-Phase Clinical Trials of Bio-Artificial Organ Technology: A Systematic Review of Ethical Issues

Abstract: Regenerative medicine has emerged as a novel alternative solution to organ failure which circumvents the issue of organ shortage. In preclinical research settings bio-artificial organs are being developed. It is anticipated that eventually it will be possible to launch first-in-human transplantation trials to test safety and efficacy in human recipients. In early-phase transplantation trials, however, research participants could be exposed to serious risks, such as toxicity, infections and tumorigenesis. So fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 112 publications
0
20
0
1
Order By: Relevance
“…Drug authorities such as the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) provide well defined and strict guidelines for pharmaceutical agents, but not cell-based bio-artificial organs such as decellularized liver grafts. Jongh et al identified prominent themes to be considered for building clinical and ethical guidelines [112]. Defining cell source, risk-benefit assessment, criteria for patient selection, design of the trial, informed consent, oversight, and accountability issues related to cell-based bio-artificial organs (e.g., recellularized liver grafts) potentially benefit from clinical trials in adjacent fields such as cell therapy.…”
Section: Regulatory and Ethical Issuesmentioning
confidence: 99%
“…Drug authorities such as the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) provide well defined and strict guidelines for pharmaceutical agents, but not cell-based bio-artificial organs such as decellularized liver grafts. Jongh et al identified prominent themes to be considered for building clinical and ethical guidelines [112]. Defining cell source, risk-benefit assessment, criteria for patient selection, design of the trial, informed consent, oversight, and accountability issues related to cell-based bio-artificial organs (e.g., recellularized liver grafts) potentially benefit from clinical trials in adjacent fields such as cell therapy.…”
Section: Regulatory and Ethical Issuesmentioning
confidence: 99%
“…A recently published systematic review highlighted the ethical challenges of conducting early phase clinical trials of bioartificial organs [ 24 ]. Of most relevance to the clinical translation of this therapy for Type 1 Diabetes patients are 1) the source of the various cells used 2) recipient selection 3) informed consent and 4) access and justice considerations.…”
Section: Part 1—ethical Legal and Psychosocial Overviewmentioning
confidence: 99%
“…First, where hybrid products combine components made from cells and tissues (biomaterial) from different sources, each source (allogenic stem cells, deceased donor human islet cells and xenogeneic cells) will come with its own set of ethical considerations [ 24 ]. We explore this in more detail in Part 2 of this paper.…”
Section: Part 1—ethical Legal and Psychosocial Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Abgesehen von der medizintechnologischen Hoffnung auf künstliche Organe ist vor allem an Ersatzorgane auf der Basis humaner pluripotenter Stammzellen zu denken. Neuere Forschungserfolge der humanen Stammzellforschung lassen diese Option auf Dauer als durchaus realistisch erscheinen ( 13 S. 221, 19 ).…”
Section: Weitere Ethische Problempunkteunclassified